In Situ Polymerization of Aqueous Solutions of NIPAAm Initiated by Atmospheric Plasma Treatment. Issue 6 (8th April 2013) - Molina, Ricardo; Ligero, Cristina; Jovančić, Petar; Bertran, Enric
Abstract In situ polymerization of aqueous solution of NIPAAm initiated by atmospheric dielectric barrier discharge (DBD) plasma treatment as an innovative approach to synthesis of thin polymeric films and hydrogels is introduced in this work. The characterization of the active species present in the polymerization plasma system by optical emission spectroscopy (OES) and UV irradiation as well as the chemical characterization of the plasma polymerized NIPAAm (PNIPAAm) films by FTIR, 1H‐NMR spectroscopy and elemental analysis give evidences that the monomer chemical composition is highly retained during the in situ polymerization.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>